Laryngeal Electromyography: Clinical Application - Robert T. Sataloff (2018)
Laryngeal electromyography (LEMG) is a valuable adjunct in clinical management of patients with voice disorders. LEMG is valuable in differentiating vocal fold paresis/paralysis from cricoarytenoid joint fixation. Our data indicate that visual assessment alone is inadequate to diagnose neuromuscular dysfunction in the larynx and that diagnoses based on vocal dynamics assessment and strobovideolaryngoscopy are wrong in nearly one-third of cases, based on LEMG results. LEMG has also proven valuable in diagnosing neuromuscular dysfunction in some dysphonic patients with no obvious vocal fold movement abnormalities observed during strobovideolaryngoscopy. Review of 751 patients suggests that there is a correlation between the severity of paresis and treatment required to achieve satisfactory outcomes; that is, LEMG allows us to predict whether patients will probably require therapy alone or therapy combined with surgery. Additional evidence-based research should be encouraged to evaluate efficacy further. © 2010 The Voice Foundation.